The Automatic Drilling System of 6R-2P Mining Drill Jumbos. (February 2015) - Wang, Yujun; Fang, Can; Jiang, Qimi; Ahmed, Syed Naeem
In order to improve the efficiency of underground mining and tunneling operations and to realize automatic drilling, it is necessary to develop the automation system for large drill jumbos. This work focuses on one such mining drill jumbo which is actually a redundant robotic manipulator with eight degrees of freedom, because it has six revolute joints and two prismatic joints. To realize the autonomous drilling operation, algorithms are proposed to calculate the desired pose of the end-effector and to solve the inverse kinematics of the drill jumbo, which is one of the key issues for developing the automation system. After that, a control strategy is proposed to independently control the eight joint variables using PID feedback control approaches. The simulation model is developed in Simulink. As the closed-loop controllers corresponding to all joints are local and independent of each other, the whole system is not a closed-loop feedback control. In order to estimate the possible maximal pose error, the analysis of the pose error caused by the errors of the joint variables is conducted. The results are satisfactory for mining applications and the developed automation system is being applied in the drill jumbos built by Mining Technologies International Inc.